Implementasi Standar Pelayanan Minimal Bidang Kesehatan Di RSUD Kota Baubau - Dedi Rahmat Saputra; Suranto Suranto (Journal of Governance and Public Policy, 2014)
The hospital has a strategic role in the effort to accelerate the improvement of  public health degree. The new para-digm of  health care requires hospitals provide quality services according to the needs and wishes of  the patient withreference to the code of  professional conduct and medical. Performance of health care organizations typically use aminimum standard criteria of  service in accordance with the Regulation of  the Minister of Health No. 741 / Menkes /Per / VII / 2008. These regulations outline covers; a) basic health services, b) health care referrals, c) epidemiologicalinvestigation and prevention of  outbreaks and d) health promotion and community development. The purpose of thisstudy was to determine the implementation of  the minimum service standards in the field of  health referral at RSUDBaubau and to determine the factors that affect the minimum service standard reference in the field of  health at RSUDBaubau. The method used in this research is descriptive qualitative. The data collection techniques in this research isinterview and documentation. Meanwhile, the techniques used to analyze the data in this study is a descriptive analysistechniques. This analysis includes data checking, data grouping, data checking, data analysis and conclusion. Theresults of  this experiment showed that the implementation of the minimum service standards in the field of  healthreferral at RSUD Baubau has been good. A slight lack of implementation of  the health sector MSS reference in RSUDBaubau is the amount of  human resources required. The factors that affect the implementation of  minimum servicestandard reference in the field of  health, namely RSUD Baubau; Communication, disposition and bureaucratic struc-ture. As for the factor of  resources because there is still a shortage of  only 80% to meet the needs of  humanresources at RSUD Baubau.